2015
DOI: 10.1016/j.msec.2015.01.039
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility and drug release behavior of scaffolds prepared by coaxial electrospinning of poly(butylene succinate) and polyethylene glycol

Abstract: Scaffolds constituted by electrospun microfibers of poly(ethylene glycol) (PEG) and poly(butylene succinate) (PBS) were studied. Specifically, coaxial microfibers having different core-shell distributions and compositions were considered as well as uniaxial micro/nanofibers prepared from mixtures of both polymers. Processing conditions were optimized for all geometries and compositions and resulting morphologies (i.e. diameter and surface texture) characterized by scanning electron microscopy. Chemical composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
81
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(82 citation statements)
references
References 33 publications
1
81
0
Order By: Relevance
“…It was clearly observed that the unloaded PBS mat with a 3D structure supports a higher cell growth than the control (2D surface of the tissue culture plate). This point is meaningful since it suggests that the mat has a structure of pores and channels similar to other scaffolds developed for tissue growth, and also that PBS has good biocompatibility [61]. On the other hand, mats loaded with indole and indole-derivatives showed inhibitory effects on proliferation of cell lines.…”
Section: Antiproliferative Activity Assaysmentioning
confidence: 71%
“…It was clearly observed that the unloaded PBS mat with a 3D structure supports a higher cell growth than the control (2D surface of the tissue culture plate). This point is meaningful since it suggests that the mat has a structure of pores and channels similar to other scaffolds developed for tissue growth, and also that PBS has good biocompatibility [61]. On the other hand, mats loaded with indole and indole-derivatives showed inhibitory effects on proliferation of cell lines.…”
Section: Antiproliferative Activity Assaysmentioning
confidence: 71%
“…High-resolution XPS spectra in the C 1s region are displayed in Figure 5, while those in the N 1s and O 1s regions are displayed in Figure 6. The three Gaussian curves derived from the deconvolution of the C 1s peak for unloaded polyester fibers correspond to the saturated C-C/C-H (284.8 eV), C-O (286.1 eV) and C=O (288.7 eV) bonds of the PE44 chains [50,51]. The three peptide-loaded PE44 fibers display an additional fourth Gaussian curve at 287.7 eV that has been attributed to the (O=)C-NH peptide bonds [52,53].…”
Section: Chemical Characterizationmentioning
confidence: 99%
“…The three peptide-loaded PE44 fibers display an additional fourth Gaussian curve at 287.7 eV that has been attributed to the (O=)C-NH peptide bonds [52,53]. On the other hand, two Gaussian curves, which correspond to the C=O (531.87 eV) and C-O bonds (533.42), were derived from the O 1s signal [50][51][52][53][54]. The intensity of the C=O component is lower than that of the C-O one for unloaded PE44, while the opposite is obtained for PE44/GA-S1, PE44/GA-S2, and PE44/GA-L due to the incorporation of peptides.…”
Section: Chemical Characterizationmentioning
confidence: 99%
“…Literature shows PBS associated with other polymers as an efficient matrix to the preparation of scaffold. [13][14][15][16] Mostly, expensive techniques, such as electro-spinning, are used to the preparation of these materials. 16 Thus, PBS was used here to prepare scaffolds by leaching using NaCl as a cheap porogenic agent.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] Mostly, expensive techniques, such as electro-spinning, are used to the preparation of these materials. 16 Thus, PBS was used here to prepare scaffolds by leaching using NaCl as a cheap porogenic agent. The obtained materials were characterized using several techniques, and the results allowed inferring that leaching is a fast, little expensive and efficient way to prepare PBS scaffolds.…”
Section: Introductionmentioning
confidence: 99%